Synthesis and Study of Chemical Delivery System for Targeting Nitrogen Mustard to the Brain - K. Singh, Rajesh; Malik, Sapna; Sharma, Deep; Prasad, D.N.; Bhardwaj, T.R.; Sumit (Asian Journal of Chemistry, 2012)
The aim of the present study is to develop the redox delivery of bis-(2-chloroethyl) amine using nicotinic acid as carrier for the site specific and site enhanced sustained delivery of alkylating anticancer moiety to the brain. Structures of all the synthesized compounds were characterized by UV, IR and 1H NMR techniques. An in vitro chemical oxidation study with silver nitrate of target compound (4) indicates that it can be readily converted into its corresponding salt (3). In vitro kinetic studies of final compound (4) in biological media showed its rate of oxidation followed pseudo-first-order kinetics with very short half-lives in rat plasma, human blood and tissue homogenate. The study of some other physicochemical parameter calculated by online software such as lipophilicity, polar surface area, rule of five, number of NH or OH hydrogen bond donors and nON value indicates that it can be permeable to blood-brain barrier.